Household and family religion in antiquity - Bodel, John P. (The ancient world comparative histories, 2008)
Introduction / John Bodel & Saul M. Olyan -- Theorizing the religion of ancient households and families / Stanley K. Stowers -- Family religion in second millennium West Asia (Mesopotamia, Emar, Nuzi) / Karel van der Toorn -- The integration of household and community religion in ancient Syria / Daniel E. Fleming -- Family, household, and local religion at late bronze age ugarit / Theodore J. Lewis -- Family religion in ancient Irael and its surroundings / Rainer Albertz -- Family religion in Israel and the wider Levant of the first millennium BCE / Saul M. Olyan -- Household religion, family religion, and women's religion in ancient Israel / Susan Ackerman -- Ashdod and the material remains of domestic cults in the Philistine Coastal Plain / R'diger Schmitt -- Household religion in ancient Egypt / Robert K. Ritner -- Household and domestic religion in ancient Egypt / Barbara S. Lesko -- Household religion in ancient Greece / Christopher A. Faraone -- Family matters : domestic religion in classical Greece / Deborah Boedeker -- Cicero's Minerva, Penates, and the mother of the Lares : an outline of -- Roman domestic religion / John Bodel -- Comparative perspectives / John Bodel & Saul M. Olyan